2011
DOI: 10.3109/13645706.2011.602691
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the sonographic appearance and anatomy of the obturator internus in normal males

Abstract: The aim of this study was to compare the appearance of the normal male obturator internus on transrectal ultrasound with anatomical examination to advance the knowledge of the male pelvic muscles. This information may help to provide a new imaging method for observation of the normal male obturator internus and may facilitate the treatment of obturator internus abscesses and various other types of interventional therapies. Ten formalin-fixed male cadavers were dissected to examine the appearance and structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Solomon et al (2010), in their study of 20 hip dissections, found OI attaching to the surrounding rami of the obturator foramen in all specimens. In addition to this, Wu et al (2012), using both ultrasonography and cadaveric dissections, identified additional attachments on the lateral pelvic wall in 15 cadavers. One textbook source further refers to the margin of the lesser sciatic notch but this may have been imprecisely redacted from a detailed anatomical study of 14 cadavers (Shinohara, 1995) which found that OI converged on "a saddle-shaped cartilage" overlying the lesser sciatic notch.…”
Section: Proximal Muscle Attachmentsmentioning
confidence: 99%
“…Solomon et al (2010), in their study of 20 hip dissections, found OI attaching to the surrounding rami of the obturator foramen in all specimens. In addition to this, Wu et al (2012), using both ultrasonography and cadaveric dissections, identified additional attachments on the lateral pelvic wall in 15 cadavers. One textbook source further refers to the margin of the lesser sciatic notch but this may have been imprecisely redacted from a detailed anatomical study of 14 cadavers (Shinohara, 1995) which found that OI converged on "a saddle-shaped cartilage" overlying the lesser sciatic notch.…”
Section: Proximal Muscle Attachmentsmentioning
confidence: 99%
“…Several Authors considered the MRI essential to the location, classification, and evaluation of the injury size 11,14 . However, is important to underline that also the US examination shows a high sensitivity and specificity in IO assessment 15 . Concerning MRI assessment some Authors suggest the use of standard high-field -1.5 or 3T 11 .…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…The suggested MRI protocol is utilization of a standard high-field (1.5 or 3 T) 11 performing PD, T2weighted, FS, and/or STIR sequences 13 in the axial, coronal, and sagittal planes 14 . However, it possible also to consider US scan 15 .…”
Section: Diagnosismentioning
confidence: 99%